Effect of Hydrophilic Polymers on Solubility Properties of Ketoprofen - 2,5-Dihydroxybenzoic Acid Multicomponent Solids - Wicaksono, Yudi; Wisudyaningsih, Budipratiwi; Priyadi, Karina Priyadi Devi Wahyu; Laily, Aisyah Prida; Putri, Salsabila Bara (Molekul, 2023)
Ketoprofen is a medicinal compound derivative of phenyl alkanoic acid that works as an anti-inflammatory, antipyretic, and analgesic. In the Biopharmaceutical Classification Systems, ketoprofen is a class II drug with high permeability but low solubility. Due to its low solubility, the absorption and bioavailability of ketoprofen are very limited, which can affect its therapeutic effectiveness. This study aimed to increase ketoprofen's solubility by forming multicomponent solids using 2,5-dihydroxybenzoic acid coformer with adding hydrophilic polymers ((hydroxypropyl)methylcellulose, polyvinylpyrrolidone K90, and polyethylene glycol 4000). The results showed that ketoprofen with 2,5-dihydroxybenzoic acid coformer prepared using the solvent evaporation method formed a eutectic mixture. Adding hydrophilic polymers to the ketoprofen - 2,5-dihydroxybenzoic acid multicomponent solid increased the crystallinity and decreased the melting point of the multicomponent solids. The multicomponent solids of ketoprofen - 2,5-dihydroxybenzoic acid with the addition of hydrophilic polymers had solubility and dissolution efficiency significantly higher (p<0.05) than the ketoprofen - 2,5-dihydroxybenzoic acid multicomponent solids without hydrophilic polymers.